2021
DOI: 10.31234/osf.io/fce8z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Earth a Perfect Square? Repetition Increases the Perceived Truth of Highly Implausible Statements

Abstract: A single exposure to statements is typically enough to increase their perceived truth. This Truth-by-Repetition (TBR) effect has long been assumed to occur only with statements whose truth value is unknown to participants. Contrary to this hypothesis, recent research found a TBR effect with statements known to be false. Of note, a recent model even posits that repetition could increase the perceived truth of highly implausible statements. As for now, however, no empirical evidence has reported a TBR effect for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although this null effect might be due to participants' lack of knowledge, prior studies have shown that the experience of fluency is still used as a valid cue for truth when knowledge about statements' content (Fazio et al, 2015;Fazio et al, 2019), source credibility (Begg et al, 1992;Unkelbach & Stahl, 2009), and declarative advice about the credibility of a statement (Unkelbach & Greifeneder, 2018) suggest the opposite. This is also in a recent study that found a truth effect for highly implausible statements, such as "earth is a perfect square", for which knowledge (of falsity) is present (Lacassagne et al, 2021).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although this null effect might be due to participants' lack of knowledge, prior studies have shown that the experience of fluency is still used as a valid cue for truth when knowledge about statements' content (Fazio et al, 2015;Fazio et al, 2019), source credibility (Begg et al, 1992;Unkelbach & Stahl, 2009), and declarative advice about the credibility of a statement (Unkelbach & Greifeneder, 2018) suggest the opposite. This is also in a recent study that found a truth effect for highly implausible statements, such as "earth is a perfect square", for which knowledge (of falsity) is present (Lacassagne et al, 2021).…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Henderson et al (2021) found a negative TBR effect for about 15% of the sample. Moreover, Lacassagne et al (2022) found that when the to-be-judged statements are selected to be highly implausible, the proportion of participants showing a negative TBR effect increased to 28%. Our findings extend this idea in that we showed that the negative TBR effect was more likely for instructed (40%) than experienced (20%) repetition.…”
Section: Discussionmentioning
confidence: 96%
“…Although this null effect might be due to participants' lack of knowledge, prior studies have shown that the experience of fluency is still used as a valid cue for truth when knowledge about statements' content (Fazio et al, 2015;Fazio et al, 2019), source credibility (Begg et al, 1992;Unkelbach & Stahl, 2009), and declarative advice about the credibility of a statement (Unkelbach & Greifeneder, 2018) suggest the opposite. This is also illustrated in a recent study that found a truth effect for highly implausible statements, such as "earth is a perfect square", for which knowledge (of falsity) is present (Lacassagne et al, 2021).…”
Section: Discussionmentioning
confidence: 74%
“…The e ect has been demonstrated for frivolous trivia questions (e.g. Hasher et al, 1977;Lacassagne, Béna, & Corneille, 2021;Unkelbach, 2007;Wang, Brashier, Wing, Marsh, & Cabeza, 2016) as well as consequential fake news headlines (Pennycook et al, 2018). The illusory truth e ect has also been shown to be robust across people with di erent levels of cognitive ability, need for cognitive closure, and cognitive styles (De keersmaecker et al, 2020).…”
mentioning
confidence: 99%